Gastric migration: a dreaded complication of Nissen fundoplicatio - Lugo, Leonel Lozano; Torres Ordaz, David Eduardo; Grande Ramirez, Cesar Ivan (International Journal of Research in Medical Sciences, 2024)
Gastric migration after laparoscopic Nissen fundoplication is one of the most feared and least expected complications, due to the fact that it overshadows the patient's prognosis, increases the surgical risk of reoperation, as well as the anatomical difficulty of recurrence in previously manipulated tissues. Objectives to carry out a bibliographic review of the surgical management, the present evidence and the projected course in the approach to this complication, based on a case report. A 68-year-old female who presented on a scheduled basis with a history of multiple episodes of vomiting, with reports of several conclusive endoscopies with moderate erosive gastropathy and hiatal hernia of 4 cm as well as pylorus, non-assessable manometry and proposed surgical event of Nissen type fundus pylorus. Gastric migration is a potentially lethal complication where the only history of Nissen type fundoplication as an antecedent in the patient should arouse sufficient suspicion to direct an approach with potential surgical outcome as the only option for a patient that even if identified early, necrosis, pneumonia and comorbidities prevent a better prognosis.